TRANSFORMING ARCHITECTURAL LEARNING INTO COMMUNITY SERVICE: A REFLECTION ON THE DESIGN OF FISHPONDS AND ISLAMIC BOARDING SCHOOL IN BANONGAN USING ACTOR-NETWORK THEORY - Akbar Fala; Agus Suharjono Ekomadyo; Eko Bagus Prasetyo (Journal of Architectural Research and Education, 2022)
According to Tri Dharma all universities in Indonesia have three essential roles comprising education, research, and community service. Every academic community is obliged to carry out and integrate these three roles. However, in reality, the development of science and technology through education and research is still often not integrated into the impactful implementation for community. As a member of academic community, an architecture student can contribute to bridge the gap between the development and the implementation of science and technology, for example by implementing architectural learning to design several social facilities using collective approach. Therefore, this research discussed the transformation of architectural learning into community service by taking a case study on the design of fishponds and Islamic boarding school in Banongan, Situbondo Regency. This qualitative research was conducted to reflect on the transformation process using the perspective of actor-network theory. The results showed that the synergy between architectural learning and community service could provide a learning space to advance pro-community architectural knowledge and produce pro-innovation social facilities for the welfare of community.